If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(x-3)+4x=-2(x+3)
We move all terms to the left:
-3(x-3)+4x-(-2(x+3))=0
We add all the numbers together, and all the variables
4x-3(x-3)-(-2(x+3))=0
We multiply parentheses
4x-3x-(-2(x+3))+9=0
We calculate terms in parentheses: -(-2(x+3)), so:We add all the numbers together, and all the variables
-2(x+3)
We multiply parentheses
-2x-6
Back to the equation:
-(-2x-6)
x-(-2x-6)+9=0
We get rid of parentheses
x+2x+6+9=0
We add all the numbers together, and all the variables
3x+15=0
We move all terms containing x to the left, all other terms to the right
3x=-15
x=-15/3
x=-5
| 4(x-3)=3(2+x) | | 4x=92x=12 | | -2(x-2)-3x=-6+5x | | 5(3/2x+6)=90 | | 2x+10=6x+40 | | 2x+7+(9/(2x-1))=0 | | 6+c/2=4 | | 5n+n=6n | | 7x+4=5x=20 | | -6(x-6)+10x=30 | | X+14+x-17+6x-5=180 | | B÷2+5=2b | | 1/3j+9=0 | | X+14+x-17=6x-5 | | 6x-5+x+14+x-17=180 | | 6x-5+x+14=x-17 | | 180=2x+5x+3x+50 | | x=2x+5x+3x+50 | | 7x-10+2x+5+2x+9=180 | | 55x-25=10x+20 | | -2=9x+12 | | 3x-5x+88x=4x+18 | | 14x-10x=3x | | -6x-2=3x+12 | | 4x-(75-x)=125 | | 4^x-8=1/1024 | | r=7/6r | | 3x+2x=7x-x | | 40+5x+x=180 | | 6a-3/2=9/2 | | 4/7x+2=22 | | 10x+80=160 |